PENDIDIKAN NILAI DALAM PEMBELAJARAN IPS MADRASAH IBTIDAIYAH DI ERA MILENIAL - Ahmad Muslich (Universitas Muhammadiyah Ponorogo, 2019)
Education is not solely so that students have knowledge but also no less important is the possession of skills and attitudes. This is because the ultimate goal of education is to change behaviour from poor to good, from less independent to independent and much more. Value education in social studies and other learning that is the aspiration of the nation's founders in the Millennium Era currently lacks examples from parents, society and national leaders. The party of democracy that raises the polarization of society is a real example that we are not serious in giving a role model for the younger generation. What is taught in school is inversely proportional to the reality of democratic and political life. Therefore it is our duty to teach value education to our young generation.